Circular RNA circTP63 enhances estrogen receptor-positive breast cancer progression and malignant behaviors through the miR-873-3p/FOXM1 axis. Issue 1 (January 2021) - Deng, Yibin; Xia, Jing; Xu, Yue-e
Abstract : Circular RNAs (circRNAs) have been shown to play a functional role in a variety of cancers. However, few studies on circRNAs in estrogen receptor-positive breast cancer have been conducted. Here, we investigated the role of circRNA circTP63 in estrogen receptor-positive breast cancer progression and malignant behaviors. First, we observed increased expression of circTP63 in MCF7 cells relative to normal human mammary epithelial cell lines, such as DU4475 and MCF-10A, and the changed oncogenicity of MCF7 cells correlated with circTP63 overexpression and downregulation. Interestingly, a series of gain- and loss-of-function assays revealed that a higher level of FOXM1 was closely associated with MCF7 malignant behaviors induced by circTP63 overexpression. Further investigations showed that circTP63 sponged to miR-873-3p, which targeted FOXM1 mRNA and inhibited its expression. Mechanistically, circTP63 binds to miR-873-3p and prevents the targeting of FOXM1, thus inducing the progression and malignant behaviors of estrogen receptor-positive breast cancer, such as cell proliferation, cell cycle dysregulation, invasion, migration and even tumor growth. CircTP63 might be a potential biomarker or target to treat estrogen receptor-positive breast cancer patients in the future. Abstract : Supplemental Digital Content is available in the text.